Informed and uninformed public opinions on CO2-capture and storage technologies in the Netherlands - de Best-Waldhober, M.; Daamen, D.; Faaij, A.P.C. (Elsevier, 2009)
Two research methods were used in this study to analyze the awareness and perception of the Dutch general public regarding Carbon dioxide Capture and Storage (CCS). In an Information-Choice Questionnaire (ICQ), a representative sample of the Dutch public (n = 995) was provided with all information on attributes of six CCS options, which experts deemed necessary to come to well-considered and well-informed opinions. A traditional questionnaire was used simultaneously (n = 327) to study uninformed evaluations of these technologies. The results showed that the Dutch public is mostly unaware of CCS and has little knowledge about how current energy use causes global warming. Uninformed respondents are still inclined to give their opinion however, which results in unpredictive, easily changeable opinions. ICQ respondents who processed information on attributes of CCS options were likely to base their option evaluations on this information, though not entirely. All in all, the results of the ICQ suggest that, after processing information deemed necessary by experts, Dutch people reluctantly agree with large scale implementation of each of the six CCS options.